Regulation of HuR by DNA Damage Response Kinases - Kim, Hyeon Ho (SAGE-Hindawi Access to Research, 2010)
As many DNA-damaging conditions repress transcription, posttranscriptional processes critically influence gene expression during the genotoxic stress response. The RNA-binding protein HuR robustly influences gene expression following DNA damage. HuR function is controlled in two principal ways: (1) by mobilizing HuR from the nucleus to the cytoplasm, where it modulates the stability and translation of target mRNAs and (2) by altering its association with target mRNAs. Here, we review evidence that two main effectors of ataxia-telangiectasia-mutated/ATM- and Rad3-related (ATM/ATR), the checkpoint kinases Chk1 and Chk2, jointly influence HuR function. Chk1 affects HuR localization by phosphorylating (hence inactivating) Cdk1, a kinase that phosphorylates HuR and thereby blocks HuR's cytoplasmic export. Chk2 modulates HuR binding to target mRNAs by phosphorylating HuR's RNA-recognition motifs (RRM1 and RRM2). We discuss how HuR phosphorylation by kinases including Chk1/Cdk1 and Chk2 impacts upon gene expression patterns, cell proliferation, and survival following genotoxic injury.